2010
DOI: 10.1007/s00125-010-1722-z
|View full text |Cite
|
Sign up to set email alerts
|

Increased protein damage in renal glomeruli, retina, nerve, plasma and urine and its prevention by thiamine and benfotiamine therapy in a rat model of diabetes

Abstract: Aims/hypothesis The aim of this study was to quantify protein damage by glycation, oxidation and nitration in a rat model of diabetes at the sites of development of microvascular complications, including the effects of thiamine and benfotiamine therapy. Methods Diabetes was induced in male Sprague-Dawley rats by 55 mg/kg streptozotocin and moderated by insulin (2 U twice daily). Diabetic and control rats were given thiamine or benfotiamine (7 or 70 mg kg −1 day −1 ) over 24 weeks. Plasma, urine and tissues wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
98
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(114 citation statements)
references
References 34 publications
(49 reference statements)
13
98
0
3
Order By: Relevance
“…It has been repeatedly demonstrated that thiamine and its analogue benfotiamine have the potential to correct most of the known metabolic abnormalities induced by high glucose in isolated cells [7][8][9] and to prevent microangiopathy in animals with experimental diabetes [10][11][12]. Besides, initial evidence shows a potential role for this vitamin also in the prevention of nephropathy in diabetic subjects [13].…”
Section: Introductionmentioning
confidence: 99%
“…It has been repeatedly demonstrated that thiamine and its analogue benfotiamine have the potential to correct most of the known metabolic abnormalities induced by high glucose in isolated cells [7][8][9] and to prevent microangiopathy in animals with experimental diabetes [10][11][12]. Besides, initial evidence shows a potential role for this vitamin also in the prevention of nephropathy in diabetic subjects [13].…”
Section: Introductionmentioning
confidence: 99%
“…Benfotiamine has shown to effect in the diabetic neuropathy patients with reduction in pain score and improve neurophysiological parameters [4]. Benfothiamine significantly reduced inflammatory (10-300 mg/kg) and neuropathic (75-300 mg/kg) nociception in non-diabetic and diabetic rats [7].…”
Section: Vol14 No 3 2018mentioning
confidence: 99%
“…Thiamine reversed hyperglycemiainduced dysfunction in cultured endothelial cells [3]. Thiamine and benfotiamine have been demonstrated in vitro to counteract the da maging effects of hyperglycemia on cultured vascular cells [4]. In addition, thiamine has been reported to improve endothelium vasodilation in patients with hyperglycemia [5].…”
Section: Vol14 No 3 2018mentioning
confidence: 99%
“…The application of benfotiamine and the resulting activation of the enzyme transketolase in the diabetic, hyperglycemic system can also produce beneficial effects on general nerve health. Benfotiamine has been shown in many preclinical [21,[31][32][33][34][35][36][37][38][39][40][41][42][43] as well as clinical studies [44][45][46][47][48][49][50][51][52][53][54][55][56][57] to prevent the formation of AGEs [21,53] and eventually with continued treatment to reverse the symptoms associated with the neuropathy [46,47,52,57]. By increasing intracellular levels of thiamine, benfotiamine indirectly induces enzymatic and biochemical pathways [58][59][60] through elevated concentrations of thiamine diphosphate resulting in a reduced level of damaging glucose-derived chemical protein species [21,22,32,[37][38][39][60][61]…”
Section: Introductionmentioning
confidence: 99%